PENGARUH POSITIONING, ADVERTISING DAN PERSONAL SELLING TERHADAP BRAND IMAGE ( CITRA MEREK ) KERIPIK KARI DI KOTA BATAM - Nofrizal N; Catur Fatchu Ukhriyawati (EQUILIBIRIA, 2014)
This study aimed to determine the effect of Positioning, Advertising and Personal Selling the Brand Image (Brand Image) Kari Chips in Batam. It is important for companies to know about it in the win market share in the city of Batam. One way to achieve competitive advantage in the market share of existing Snatch is to establish a good brand image in the eyes of consumers.The data used in this study were obtained from questionnaires (primary) and some observations as well as interviews with the producer and owner of a business owner Kari chips. The analysis technique used is multiple regression using a hypothesis test, the t test (Partial).From this study it can be concluded that the statistical test based on three variables: the variable Positioning, Advertising and Personal Selling has a positive influence on brand image.